Numerical simulation of the porous filter properties for the internal arc mollifying effects - Rochette, D. (2011)
A mathematical model and numerical experiments of pressure wave impacts with a porous medium are presented to simulate the valve burst out of a medium voltage switchgear and to evaluate the protection ﬁlter efﬁciency. A simpliﬁed one-dimensional gas ﬂow model in porous medium with variable porosity is used. To solve numerically the governing equations, we employed the numerical method presented in Rochette et al. (2005) [18] to take into account the non-conservative term P(∂ /∂x). Three sets of test are performed to study several ﬁlter prototypes. The objective is to provide a ﬁlter which does not produce a high reﬂected wave and cools enough the ejected hot gas. We ﬁrst consider ﬁlters with variable porosity and simulate the interaction with an incident pressure wave, then we consider two types of granular material to characterize their incidence on the ﬂow and ﬁnally, we simulate two different ﬂuid ﬂows (air and SF6) going through the porous medium.